New possibility of application of bacteriophages to prevent infectious complications in free skin grafting (bacteriophages in skin grafting) - V. V. Beschastnov; M. G. Ryabkov; T. N. Yudanova; I. V. Pavlenko; A. E. Leont’ev; A. A. Tulupov; V. V. Kichin (Бюллетень сибирской медицины, 2021)
Aim. To prevent infectious processes in the area of a recipient wound in free skin grafting with a split-graft.Materials and methods. A method was developed for immobilizing bacteriophages in the area of split thickness skin grafts through transferring a solution containing bacteriophages into a gel form. Microbiological and clinical studies of the effectiveness of the proposed method were performed.Results. The viability of bacteriophages in a gel dressing for up to 4 days was confirmed, as well as the reduced likelihood of local infectious complications in skin grafting.Conclusion. The gel composition containing bacteriophages allows quick response to changes in current hospital microflora and effectively counteract the dangers of nosocomial infection.